2016
DOI: 10.1111/ajgw.12230
|View full text |Cite
|
Sign up to set email alerts
|

Stilbene profiles in different tissues ofVitis viniferaL. cv. Cabernet Sauvignon and a comparison of their antioxidant activity

Abstract: Background and Aims: Stilbenes are an important group of phenolic substances that exist in roots, stems, leaves, skins and seeds. But little work has been performed to characterise the composition of grape root or to measure the antioxidant capacity of several stilbenes with hydroxyl radicals,1,1-diphenyl-2-picrylhydrazyl and nitric oxide free radicals. Methods and Results: Stilbenes were analysed by HPLC-MS/MS, and the radicals scavenging ability was determined by electron paramagnetic resonance. The root con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…studied by Pawlus et al [16]. The putatively identi ed miyabenol C, hopeaphenol, and ε-viniferin were the most prevalent stilbenoids observed in this study, which was like previous observations [10,[14][15].…”
Section: Root Stilbenoid Levelssupporting
confidence: 89%
See 2 more Smart Citations
“…studied by Pawlus et al [16]. The putatively identi ed miyabenol C, hopeaphenol, and ε-viniferin were the most prevalent stilbenoids observed in this study, which was like previous observations [10,[14][15].…”
Section: Root Stilbenoid Levelssupporting
confidence: 89%
“…A total of eleven stilbenoids were putatively identi ed in this study, and each compound was analyzed by week and year separately ( Table 1). The stilbenoid compounds quanti ed in this study were similar as those found in other studies (Table 1), albeit the resveratrol glycoside piceid was not observed in quanti able amounts, with only trace characteristic ions observed by LC-MS, despite being observed previously [10,14]. However, piceid also was not present in su ciently quanti able amounts in V. vinifera by Lambert et al [15] or in many of the wild Vitis spp.…”
Section: Root Stilbenoid Levelssupporting
confidence: 87%
See 1 more Smart Citation
“…Another compound correlated to the antioxidant capacity of the extracts was trans ‐resveratrol‐glucoside, although this compound was found at lower concentrations than flavan‐3‐ols. This compound has demonstrated DPPH scavenging capacity in other studies (Wei, Zhao, Li, & Xue, ), while its isomer, cis ‐resveratrol‐glucoside showed less efficiency in the mechanism of transfer of an atom of hydrogen to the free radicals (Mikulski, Górniak, & Molski, ).…”
Section: Resultsmentioning
confidence: 83%
“…This compound has demonstrated DPPH scavenging capacity in other studies (Wei, Zhao, Li, & Xue, 2016), while its isomer, cisresveratrol-glucoside showed less efficiency in the mechanism of transfer of an atom of hydrogen to the free radicals (Mikulski, Górniak, & Molski, 2010).…”
Section: Correlation Between Antioxidant Capacity and Phenolic Compmentioning
confidence: 88%